2018
DOI: 10.1007/s00248-018-1180-6
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for Plants? Growth Promotion by the Entomopathogenic Fungus Beauveria bassiana Depends on Nutrient Availability

Abstract: Cultivation of crops requires nutrient supplements which are costly and impact the environment. Furthermore, global demands for increased crop production call for sustainable solutions to increase yield and utilize resources such as nutrients more effectively. Some entomopathogenic fungi are able to promote plant growth, but studies over such effects have been conducted under optimal conditions where nutrients are abundantly available. We studied the effects of Beauveria bassiana (strain GHA) seed treatment on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 36 publications
1
59
0
2
Order By: Relevance
“…Our results showed that inoculation with EF produced seedlings with greater height and weight. Results from this study is in agree with others, where EF was able to promote plant growth parameters (Bamisile et al, 2018;Enkerli, 2016, Tall andMeyling, 2018), but in other cases, differences in growth parameters were not significant (Tefera and Vidal, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that inoculation with EF produced seedlings with greater height and weight. Results from this study is in agree with others, where EF was able to promote plant growth parameters (Bamisile et al, 2018;Enkerli, 2016, Tall andMeyling, 2018), but in other cases, differences in growth parameters were not significant (Tefera and Vidal, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Renuka et al (2016) observed that stems of Z. mays were also colonized by B. bassiana; however, the availability and persistence on the plant tissues varied according to their age (high persistence in young tissues). Despite several authors have demonstrated that B. bassiana as endophyte of maize, others have been revealed that after the inoculation of this EPF on maize seeds, no colonization of plant tissues was obtained (Tall and Meyling 2017).…”
Section: Resultsmentioning
confidence: 87%
“…There are multiple reports of effects on insects where retrieving of the fungus from the host plant failed, maybe due to the limited growth of the fungus within the host plant [ 13 ]. Also, methods for screening and quantifying endophytic colonization vary greatly and come with several caveats such as contamination problems [ 12 ] and underestimation of colonization [ 74 ]. Endophytic colonization has in previous studies been assumed without testing for colonization [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%